USE OF DIGITAL TECHNOLOGY IN EDUCATION PROCESS - Kasimova Mukhayo Alaevna (Journals Park Publishing, 2025)
The integration of digital technology in the education process has transformed traditional teaching and learning methods, fostering a more interactive, flexible, and student-centered environment. This paper explores the various ways digital tools—such as e-learning platforms, virtual simulations, learning management systems (LMS), and mobile applications—enhance instructional delivery and learner engagement. It also examines the benefits and challenges of implementing digital technologies in diverse educational settings, highlighting their role in promoting accessibility, inclusivity, and personalized learning. The study underscores the importance of teacher training, infrastructure development, and policy support for the effective adoption of digital education.
Keywords: Digital technology, E-learning, Online education, Distance learning, educational innovation.